Testes and Ovaries Functional and Clinical Differences and Similarities - Darwish, Atef M. (IntechOpen, 2017)
Male and female reproductive system similarities as well as differences should be taken into consideration by all scientists interested in this field. Some embryological, anatomical, histological, and clinical examples are addressed in this book. The message of the book is to increase orientation of all scientists interested in the field of similar and dissimilar issues in males and females. Reading this book will lead to a better understanding of management of both sexes, and the understanding of infertility that will hopefully reduce the effort, the time, the psychological, and the financial burden of the infertile couple and the society at large.